'I will walk out of here': Qualitative analysis of older rehabilitation patients' perceptions of mobility. (25th February 2020) - Kozica‐Olenski, Samantha; McRae, Prue; Bew, Paul; Mudge, Alison
Abstract: Objectives: To understand the motivation of older rehabilitation inpatients for mobilisation, and identify barriers and enablers to greater mobilisation. Methods: Qualitative semi‐structured interviews were conducted with older rehabilitation inpatients. All interviews were audio‐taped, transcribed verbatim and analysed using thematic and inductive techniques. Results: From 23 interviews, we found that older patients strongly value mobilisation during rehabilitation admission, to get better and maintain identity, personhood and meaningful connections. At the patient level, mobilisation was impacted by patient's confidence, family support and symptom management. At the organisational level, barriers to mobilisation included lack of timely staff support, inflexible routines, limited social opportunities, lack of physical resources, and poor communication. Conclusions: Recognising and understanding motivators, enablers and barriers to mobilising during subacute hospitalisation of older patients is an essential step towards developing and implementing successful strategies to promote greater mobilisation. Addressing mobilisation barriers requires a multifaceted approach at the patient and organisational level.